Cellular Architecture of Spinal Granulomas and the Immunological Response in Tuberculosis Patients Coinfected with HIV - Bhattacharya, Debapriya; Danaviah, Siva; Muema, Daniel M.; Akilimali, Ngomu Akeem; Moodley, Prashini; Ndung’u, Thumbi; Das, Gobardhan (Frontiers in Immunology, 2017)
Mycobacterium tuberculosis (M.tb) and HIV are individually responsible for the most deaths worldwide among all infectious agents, and co-infection with M.tb and HIV is a significant public health challenge in the developing world. Although the lung is the primary target organ for tuberculosis (TB), M.tb can also cause extra-pulmonary tuberculosis (EPTB) such as in the bones and joints. Treatment of EPTB is much more challenging than treatment of pulmonary TB. The hallmark of the host immune response against TB is the formation of organized structures called granulomas that are infiltrated with immune cells and are rich in cytokines and chemokines. Inside granulomas, the host confines the M.tb bacteria to a particular region of the organ and avoids dispersion. In this study we analyzed immune cells in bone granulomas of patients with EPTB that are also co-infected with HIV. We found that HIV-infected TB patients have dispersed bone granulomas, with reduced T cell numbers and a concomitant increase in plasma cells. Additionally, HIV-infected patients exhibited dramatically increased serum levels of IgM and IgG1 antibodies, which is indicative of T-cell-independent B-cell activation and mucosal T-cell activation, respectively. Interestingly, we also observed that CD29+ stem cells are increased in HIV-TB co-infection, suggesting a link with HIV infection. Therefore, our work provides new insights into the architecture of spinal TB granulomas and the role of B-cells and humoral immunity against a highly infectious intracellular pathogen. We propose that our findings will inform biomarker identification for EPTB and possibly the development of related therapeutics and/or vaccines to protect HIV-infected patients against disseminated TB.